PERENCANAAN KOMUNIKASI PEMASARAN TERPADU ASIAN GAMES 2018 SEBAGAI NATION BRANDING - Ayu Septiana Wardani; Reni Dyanasari (Metacommunication: Journal of Communication Studies, 2019)
In addition to acting as a government system, the Indonesian state also acts as a brand that makes it necessary to make efforts to nation branding. Sport mega event is one way to build nation branding. Indonesia was trusted to host the Asian Games 2018. By being in charge of holding a sport mega event (SMEs), Indonesia will gain some benefits from global publicity that can be used to build nation branding. Indonesia's success in holding the Asian Games 2018 has made a positive impact on Indonesia's nation branding. In the implementation of SMES, integrated marketing communications is one of the important factors that determine its success. Indonesia's success in using the Asian Games 2018 moment to build nation branding attracted the attention of researcher to conduct research on the Asian Games 2018 integrated marketing communications planning as a means of building nation branding using qualitative methods. The results of this study indicate that Indonesia implemented six steps in zero based integrated marketing communications planning. When conducting a promotion based on this plan, INASGOC also applies two steps in building Indonesia’s nation branding and communicating the values that Indonesia have through three components in the Nation Brand Hexagon.Keywords: Asian Games, INASGOC, Promotion, Nation Branding, Indonesia